Tekstualisasi al-Qur’an: Antara Kenyataan dan Kesalahpahaman - Syamsuddin Arif (TSAQAFAH, 2016)
In recent decades al-Qur’an has been the subject of increasing interest among scholars in the Muslim world as well as in the West. One of the most important issues that most researchers are dealing with pertains to its textualization –that is, how al-Qur’an was transformed from oral tradition into the written text as we have it today; how the Revelation was received and recorded, circulated and passed down from generation to generation, in both the ancient way of memorization and through the methods of reading and writing, as rigorously and accurately as it should be. Although initially the contents of al-Qur’an were widely distributed in the memories of men (i.e. the Prophet and his Companions), they were also written down piecemeal on various materials. The compilation and codification of the al-Qur’an was accomplished under the authority of Caliph Abu Bakr, and the standard codex (al-muṣḥâf al-imâm) was produced during the Caliphate of Utsman in order to bring consensus among the Muslim community both with regard to recitation and orthography (al-Rasm al-‘Utsmâniy). Given its paramount importance in Islam, the history of Qur’anic text will remain of perennial interest to both Muslim and non-Muslim researchers as it could be manipulated, distorted or exploited by those pursuing their own goals for polemical or political reasons. The present article addresses such concerns with a view to separating the wheat from the chaff in the textual history of al-Qur’an.